MANAJEMEN KELAS DALAM MENINGKATKAN DISIPLIN SISWA PADA SEKOLAH DASAR NEGERI KABUPATEN ACEH BARAT - Rajinawati Rajinawati; Saifulbahri Saifulbahri; Najmuddin Najmuddin (Puteri Hijau : Jurnal Pendidikan Sejarah, 2024)
Rajinawati, Class management in improving student discipline at West Aceh District Public Elementary Schools. The aims of this research are 1) To find out the types of classroom management applied in improving student discipline at State Elementary Schools in Cluster 1, Meureubo District, West Aceh Regency 2) To find out how classroom management is applied in improving student discipline at State Elementary Schools in Cluster 1 Meureubo District, West Aceh Regency. 3). To find out what obstacles schools face in implementing classroom management in improving student discipline in Cluster 1, Meureubo District, State Elementary School in Cluster 1, Meureubo District, West Aceh Regency. This research uses a qualitative descriptive method. The focus of this research is State Elementary Schools (SDN) in cluster 1, Aceh Regency District. The number of subjects in this research was 20 people consisting of class III teachers, school principals, and school supervisors and school committee members. Data collection techniques used include observation, interviews and documentation. The results of the data analysis concluded that the types of classroom management applied in improving student discipline at West Aceh Regency State Elementary Schools can generally be summarized into 4 (four) stages, namely the types of management planning, organization, actuating controlling. Specifically, the types of management referred to include time/discipline management, administrative management, management management, student management, collaborative management with parents/guardians, school committees, school residents and supervisory management. The implementation of classroom management in improving student discipline at State Elementary Schools in SDN Cluster 1 Meureubo District has been running according to the condition of the available facilities and infrastructure. The application of classroom management in improving students' learning discipline, namely entering class on time, doing assignments and collecting assignments given by the teacher on time, bringing notebooks according to the subject (schedule), and not talking to friends during lessons. If you look at the existing class management, the management at SDN Cluster 1 Meureubo District is quite optimal and quite good. Obstacles faced by schools in implementing classroom management to improve student discipline include violations of school rules, lack of student discipline, limited learning facilities, limited teacher resources who have not received training related to classroom management and other obstacles such as lack of parent participation in learning. children are still limited to discharging their responsibilities.